(untitled) (Forum for Linguistic Studies, 2024)
The Indian economy, marked by its rapid growth and increasing global integration, faces unique challenges amid the escalating geopolitical tensions between Israel and Iran. This paper explores the multifaceted implications of these tensions on India’s economic resilience, particularly focusing on trade dynamics, energy security, and investment strategies. As a major importer of crude oil from the Middle East, India’s economic stability is closely tied to fluctuations in oil prices influenced by regional conflicts. The analysis highlights the government’s proactive measures, including the diversification of energy sources, enhancement of diplomatic relations, and promotion of domestic manufacturing through initiatives like "Make in India." These strategies aim to mitigate risks associated with external shocks while fostering sustainable growth. By synthesizing data from trade reports and policy analyses, this research underscores the importance of a balanced diplomatic approach and strategic economic planning in navigating the complexities of international relations. Ultimately, this study provides insights into how India can leverage its strengths to enhance resilience in the face of geopolitical crises, ensuring long-term economic stability and growth amid a turbulent global landscape.